Feeding habits of yellow puffer (xenopterus naritus) at Batang Saribas - Tan, Siang Na (Universiti Malaysia Sarawak (UNIMAS), 2004)
The food choice of yellow puffer, Xenopterus naritus and the influence if physico-chemical water parameters and availability of zooplankton upon its high congregation in Batang Seribas near Kampung Manggut during certain month in a year was investigated. Thirty one stomachs were observed and 13 taxa food items were identified in the fish guts. The food preference of yellow puffer revolved around juvenile gastropod, adult gastropod, nematode, amphipod and calanoid copepod. Meio-macrobenthos was an important prey of the yellow puffer. This species in omniverom relying primarily on benthic invertebrates as their food. Congregation of this fish in the estuary of Btg. Saribas is due to the spawning activities. It is believed that the physico-chemical of the water and food availability is also influence the congregation of the fish in the area.